Dampak Kredit P4K terhadap Pendapatan dan Pengeluaran Keluarga Petani di Kabupaten Grobogan - Helmy, Zahron (Universitas Sebelas Maret, 2004)
The research of credit Impact for Rural Income Generation Project (RIGP) on Family Farmers Income and Expenditure is aimed to know program impact to educational aspect, family-member health and SFFs community social activity. And economically the research also have purpose to know credit impact on venture volume, income, family consumption, as well on employment and income distribution.The research is conducted in Grobogan District Central Java, on 222 SFFs, 12 sub-districts, 42 villages, and 44 Small Farmer Group (SFGs) of RIGP program participant, by using descriptive analysis, regression analysis model, and Gini Index as well poverty index.The research result shows descriptively occurred significant quite improvement for physical condition and SFFs family environment of RIGP program participant, which shown by the higher family-member percentage following formal education level, higher utility percentage of health facility and SFFs behavior change for participating in community social activity in their village.Based on statistical calculation it is obtained tat low category credit value impact on SFFs employment (t-cal=4.143), which have impact on income (t-cal=1.839). But high category credit value, the credit addition even reducing SFFs employment itself (t-cal=2.133). This is caused by for uncreating market, marketing network and product/venture diversification from SFFs. For middle category credit value, credit value impact on venture volume (t-cal=2.051), which has impact on consumption (t-cal=2.439).While SFFs income distribution of RIGP participant in Grobogan District it is obtained value (GC=0.32), be in middle inequality (GC=0.30 to 0.40), which means that relative income less spread unaveragely in each SFFs program participant. And for middle category credit, GC value is relative higher compared to high and low category credit value, namely as large as (GC=0.35). This value shows that income distribution for each SFFs of middle category credit receiver exists significant quite income inequality, which reative higher than high and low category credit value receiver SFFs.Furthermore, based on poverty standard of Grobogan District which measured based on income per capita/month as large as Rp. 74.007,- it has been achieved value 51,35% credit receiver SFFs still be in poor condition, with the lowest inequality level on high category credit receiver as large as PG=0,1801.